Conceptual Study on Change Management Approaches and Strategies in ERP Implementations: Overcoming Resistance in ERP Implementation with Effective Change Management Strategies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Recent advancement in information technology and business development, the business organizations turned towards the adoption of advanced information technology systems for their organizational setup. Progression of technologies in business environment has been observed in many organizations by the initiation of enterprise resource planning (ERP) system implementation. ERP is business integrated information system software that attracts the attention of business organizations in order to improve their business processes and achieve the company’s goals. Almost all the ERP system implementation is based on change management system, where the traditional legacy system is completely replaced with the new and advance system. When implementing an enterprise resource planning (ERP) system, top management commonly faces an unwanted attitude from potential users for one reason or another, they resist the implementation process. Top management should, therefore, proactively deal with this problem instead of reactively confronting it.